Unit for Splitting Degraded Mountain Meadows and Pastures Based on a Mini Tractor - S. M. Dzhibilov; L. R. Guluyeva (Сельскохозяйственные машины и технологии, 2022)
Soil splitting is used to prevent water and wind erosion of soils, improve their water-air regime in mountain meadows and pastures. It reduces soil loss, improves plants moisture supply, affects herbage species composition and increases fodder lands yield. The advantages of a small-sized unit have been described ensuring gentle splitting with the formation of water-absorbing splits on the slopes. (Research purpose) To create a small-sized maneuverable splitter for mountain meadows and pastures, to determine its agrotechnical parameters, to give a graphic-analytical substantiation of the splitting working process in areas with a slope of up to 12 degrees. (Materials and methods) A technical examination of the unit laboratory sample was carried out at an altitude of 1540 meters above the sea level. The slitter working width was determined by two passes at 25 points located at the intervals of at least 1 meter in the unit movement direction. (Results and discussion) A splitter for the mountain area was built on the basis of a Feng Shou 180 mini-tractor, reducing the load on the soil. An optimal arrangement scheme for the splitter working bodies has been developed when moving along a slope. The scheme of the unit movement on the slope was substantiated. The following technological parameters were set: the distance between the splits is 1,000 millimeters, the depth of slip cutting is 200220 millimeters, the split width is 10-30 millimeters. (Conclusions) It was determined having penetrated into the soil, the shift in the reaction of the working body located on the slope top side of the tractor axis stabilizes the position of the unit when moving across the slope, preventing it from sliding down. It was found that being 1,000 mm apart from each other and of the width of not more than 35 mm, the splitter cutting-knives do not destroy the turf layer, do not damage the edges of the slot. The use of a Feng Shou 180 mini-tractor enabled to decrease the unit weight load of on the agrocenosis during movement.